Purification and characterization of the cytochrome oxidase from alkalophilic Bacillus firmus RAB. - Kitada, M (1984)
A cytochrome oxidase was purified 52-fold from membranes of alkalophilic Bacillus firmus RAB by extraction with Triton X-100, ion-exchange and hydroxyapatite chromatography, and gel filtration. On denaturing gels, the purified enzyme dissociated into two subunits of 56,000 and 40,000 Mr as well as a cytochrome c with an Mr of approximately 14,000. Heme contents calculated for an enzyme with a molecular weight of 110,000 were found to be 2 mol of heme a and 1 mol of heme c per mol of cytochrome oxidase; approximately 2 mol of copper per mol of purified enzyme was also found. Enzyme activity was observed in assays using reduced yeast or horse heart cytochrome c. Activity of the purified enzyme was optimal at pH 6.0 and in the presence of added lipids. Impure, membrane-associated activity exhibited a broader pH range for optimal activity extending to alkaline values.